Purification of pancreatic endocrine subsets reveals increased iron metabolism in beta cells - C. Berthault; W. Staels; R. Scharfmann (Elsevier, 2020)
Objectives: The main endocrine cell types in pancreatic islets are alpha, beta, and delta cells. Although these cell types have distinct roles in the regulation of glucose homeostasis, inadequate purification methods preclude the study of cell type-specific effects. We developed a reliable approach that enables simultaneous sorting of live alpha, beta, and delta cells from mouse islets for downstream analyses. Methods: We developed an antibody panel against cell surface antigens to enable isolation of highly purified endocrine subsets from mouse islets based on the specific differential expression of CD71 on beta cells and CD24 on delta cells. We rigorously demonstrated the reliability and validity of our approach using bulk and single cell qPCR, immunocytochemistry, reporter mice, and transcriptomics. Results: Pancreatic alpha, beta, and delta cells can be separated based on beta cell-specific CD71 surface expression and high expression of CD24 on delta cells. We applied our new sorting strategy to demonstrate that CD71, which is the transferrin receptor mediating the uptake of transferrin-bound iron, is upregulated in beta cells during early postnatal weeks. We found that beta cells express higher levels of several other genes implicated in iron metabolism and iron deprivation significantly impaired beta cell function. In human beta cells, CD71 is similarly required for iron uptake and CD71 surface expression is regulated in a glucose-dependent manner. Conclusions: This study provides a novel and efficient purification method for murine alpha, beta, and delta cells, identifies for the first time CD71 as a postnatal beta cell-specific marker, and demonstrates a central role of iron metabolism in beta cell function.